Tanah Adat dan Kearifan Lingkungan Orang Melayu - Husni Thamrin (Universitas Riau, 2015)
In the lives of many Malay expression an expression pointing to a festive, eitherverbally or written about environmental conservation. The expression of the phrase has longbeen awake in the institutional culture and Malay poeple. But the values and norms havelargely cut out in the life of a day to day. This is due to the institutional system of Malay isnot acting as it should. This caused a capitalistic environment management policies and theantropocentric paradigm in form since the days of colonialism, up until this point.